Development of Early Grade Indonesian E-Modules Using the Kvisoft Flipbook Maker Application - Juni Agus Simaremare; Emelda Thesalonika (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This article aims to 1) Produce products in the form of e-modules for Early Class Indonesian courses using the Kvisoft Flipbook Maker Application; 2) To find out the feasibility of developing an e-module based on the Kvisoft Flipbook Maker Application in the Early class Indonesian language course; 3) To find out students' responses to the development of e-modules based on the Kvisoft Flipbook Maker application in the Early Grade Indonesian course. The type of research conducted is research and development (R&D). The development model used in this study is a 4-D development model (four D Model), namely define activities, design activities, development activities and are validated by experts and see the practicality of e-module products. 1) The results of material expert validation obtained an average of 86% in the very feasible category. Second, media experts get an average of 93% in the very decent category. Third, linguists get an average of 87% with a very decent category. Then, in individual trials, students responded to this e-module in the very good category with an average percentage of 93%. In the small group trial, the students' responses were in the very good category with an average percentage of 92.25%. Meanwhile, in the limited field group trial, the criteria of